PENERAPAN STRATEGI ARCS DENGAN PEMBERIAN SCAFFOLDING : UPAYA MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIKA DAN PEMBENTUKAN KARAKTER MAHASISWA PADA MATA KULIAH MATEMATIKA DASAR - Henny Ekana Chrisnawati; Budi Usodo; Ira Kurniawati; Yemi Kuswardi (Universitas Sebelas Maret, 2015)
ABSTRACT This research has purposes to increase mathematical understanding ability and build character of undergraduate in mathematics foundation which uses ARCS’s strategy with giving scaffolding. Mathematics foundation which has abstract’s characteristic and necessary from understanding ability both computational also fungtional become priority of researcher’s thought. Characteristic of mathematical concept which is pyramidal compel students to understanding basic concept correctly for the sake of understanding new concept. Not only for understanding but also building character is one of affectionate factors priority to reach success in learning mathematics. Pay attention of developing character, undergraduate are wished to show positively character in learning so that gives positively implication to the results. This research is classroom activity research which gives some informations about the changes or increase that ae caused by an activity. This research uses undergraduate of physics education in year academic 2015/2016 as a subject. Technique of collecting data uses test and observation while learning and research’s instrument is developed by validation of professional judgment. The result from application of ARCS’s strategy with giving scaffolding in learning is exist an increase of mathematical understanding ability. It showed by the results of mathematical understanding ability’s test in first and second cycle which gave information that there exist an increase of completeness percentage for understanding mathematical concept which from 39, 5 % up to 77,4 % in first cycle then continued up to 82,6 % in second cycle. Like that, it also showed by the mean of the test’s result which gave an increase from 61 in first cycle up to 81,1 in second cycle. The application of ARCS’s strategy also increased the affectionate learning’s result. It showed by the results of observation in first and second cycle which showed that the mean percentage of character building from indicators: honest, discipline, hardworking, creative, stand alone, has a curiosity, appreciate achievement, friendly, responsible which were developed. Those results increase from bottom category in pre-cycle became in middle and high category in second cycle. It means that used motivation technique (attention, relevance, confidence and satisfaction) in learning activity of mathematics foundation gave fact that those technique fulfilled need of undergraduate for reaching optimal achievement. Keywords : understanding concept ability, character, ARCS’s strategy, scaffolding